Mycoses of implantation in Latin America: an overview of epidemiology, clinical manifestations, diagnosis and treatment (2011)
ABSTRACT: Implantation or subcutaneous mycoses are a frequent health problem in Latin American countries and other tropical and subtropical areas. Although such infections rarely cause disseminated or invasive disease, they have an important impact on public health, and timely diagnosis and appropriate treatment remain important. Although some implantation mycoses are found in immunocompromised persons, the immunocompetent population is the principal target in Latin America. Most etiologic agents are found in soil, vegetation, and decaying matter in tropical, subtropical, and humid environments and infection is commonly the result of penetrating injury. Infections primarily occur (1) among low socioeconomic groups, (2) among those living in rural areas or involved in farming, hunting, or other outdoor activities, and (3) particularly among adult men. This review focuses on the epidemiology of the most clinically significant implantation mycoses in Latin America, i.e., sporotrichosis, eumycetoma, chromoblastomycosis, subcutaneous phaeohyphomycosis, subcutaneous zygomycosis, and lacaziosis. Main epidemiologic findings, clinical manifestations, diagnosis, and treatment options are also discussed.